Integrated self-validating thermocouples with a reference temperature up to 1329 °C. (31st August 2018) - Tucker, Declan; Andreu, Aurik; Elliott, Claire; Ford, Trevor; Neagu, Marius; Machin, Graham; Pearce, Jonathan
Abstract: Thermoelectric instability, or calibration drift, is a major problem for users of thermocouples at high temperature. NPL, in collaboration with CCPI Europe, AFRC and ICPE-CA/BRML-INM has designed, made and industrially tested Type S thermocouples with integrated temperature fixed-point cells. These in situ, self-validating thermocouples (denoted 'inseva') have the same external dimensions as conventional industrial thermocouples (the recrystallised alumina sheath has an outer diameter 7 of mm). The device can be used to detect the melting and/or freezing temperature of the integrated temperature fixed-point ingot, which enables a self-validation to be performed whilst in situ . During the testing, three different reference ingots were used in the cells, namely: copper (1084 °C), cobalt-carbon (1324 °C) and nickel-carbon (1329 °C). The metrological performance for two iterations of the design are presented, with an emphasis on the ability of the inseva thermocouples to indicate their own thermoelectric stability. A measurement uncertainty budget is also given for the case of a Ni–C inseva thermocouple. This paper demonstrates that inseva thermocouples can be successfully validated during industrial processes through the observation of the melting plateau, as well as their robustness over time in industrial conditions. A key finding is that the Ni–C eutectic alloy is much more robust than the Co–C eutectic alloy for the used type of graphite crucible, making the Ni–C inseva thermocouple more suitable for industrial applications, and a good alternative.